Evolution and financial cost of socioeconomic inequalities in ambulatory care sensitive conditions - Dimitrovová, Klára (2018)
Background: Hospitalizations for Ambulatory Care Sensitive Conditions (ACSC) are specific conditions for which hospitalization is thought to be avoidable through patient education, health promotion initiatives, early diagnosis and by appropriate chronic disease management, and have been shown to be greatly influenced by socioeconomic (SE) characteristics. We examined the SE inequalities in hospitalization rates for ACSC in Portugal, their evolution over time (2000-2014), and their associated financial burden. Methods: We modeled municipality-level ACSC hospitalization rates per 1000 inhabitants and ACSC hospitalization-related costs per inhabitant, for the 2000-2014 period (n = 4170), as a function of SE indicators (illiteracy and purchasing power, in quintiles), controlling for the proportion of elderly, sex, disease specific mortality rate, population density, PC supply, and time trend. The evolution of inequalities was measured interacting SE indicators with a time trend. Costs attributable to ACSC related hospitalization inequalities were measured by the predicted values for each quintile of the SE indicators. Results: Hospitalization rate for ACSC was significantly higher in the 4th quintile of illiteracy compared with the 1st quintile (beta = 1.97; p < 0.01), and significantly lower in the 5th quintile of purchasing power, compared with the 1st quintile (beta = - 1.19; p < 0.05). ACSC hospitalization-related costs were also significantly higher in the 4th quintile of illiteracy compared with the 1st quintile (beta = 4.04€; p < 0.05), and significantly lower in the 5th quintile of purchasing power, compared with the 1st quintile (beta = - 4,69€; p < 0.01). The SE gradient significantly increased over the 2000-2014 period, and the annual cost of inequalities were estimated at more than 15 million euros for the Portuguese NHS. Conclusion: There was an increasing SE patterning in ACSC related hospitalizations, possibly reflecting increasing SE inequalities in early and preventive high-quality care, imposing a substantial financial burden to the Portuguese NHS.